Uji Efek Antioksidan Formulasi Sediaan Sirup Ekstrak Etanol Kulit Buah Jeruk Bali (Citrus Maxima Merr.) Terhadap Malondialdehid Tikus Putih (Rattus Novergicus) Yang Diinduksi Karbon Tetraklorida - Suryanita Suryanita; Hasma Hasma (Media Kesehatan Politeknik Kesehatan Makassar, 2021)
Free radicals are any molecule or atom that is unstable because it has one or more unpaired electrons. Free radicals that are formed in the body will produce new free radicals through a chain reaction which eventually increases in number and attacks the body's cells so that tissue damage will occur, therefore antioxidants are needed from outside to neutralize free radicals, the salute is grapefruit peel (Citrus maxima Merr.) This study aims to determine the antioxidant activity of the ethanol extract syrup of grapefruit peel against levels of Malondialdehyde (MDA) blood plasma of male white rats induced by carbon tetrachloride (CCl4). The stages of this study were the first to make a skin extract syrup. grapefruit peel containing 1% extract (F1), 2% extract (F2), 3% extract (F3), and without grapefruit peel extract (F4) as negative control; Furthermore, testing the stability of the syrup preparations before and after storage was accelerated for 12 cycles, and finally the syrup with the best stability was tested for its lipid peroxidation inhibition activity in vivo with blood plasma MDA levels in rats induced by Carbon Tetrachloride. The results showed the results of the syrup stability test. indicates that F3 has the best stability. As for the in vivo test results, F3 showed a decrease in the MDA level of blood plasma in rats which was significantly different from the negative control. The grapefruit peel significantly decreased the MDA level of the rat blood plasma with a  value p<0.05. Keywords : Free radicals, Grapefruit Peel, Antioxidant, Syrup Preparation, Malondialdehyde (MDA)